Development of a wireless sensor for vibration measurement I - Lin, Junhao (Nanyang Technological University, 2024)
This report outlines the design, development, and implementation of a novel wireless sensor system dedicated to the measurement of vibrations in diverse environments. The primary objective of this project was to create a versatile and efficient tool capable of wirelessly monitoring vibrations in real time, providing valuable data for various applications, including monitoring vibrations on railway tracks. The passage of trains over railway tracks generates vibrations that can have significant effects on both the infrastructure and nearby surroundings. One of the effects is track Degradation. Repeated train passages contribute to wear and tear on the tracks, leading to track degradation over time. This may result in increased maintenance requirements and associated costs. The wireless sensors incorporate accelerometers and wireless communication technology to enable seamless and remote data acquisition. Utilizing low-power consumption components, the sensor ensures prolonged battery life while maintaining accurate and reliable measurements. The wireless capability allows for flexible deployment in hard-to-reach or hazardous locations, facilitating comprehensive monitoring without the need for extensive wiring. The development process involved thorough testing procedures with shaker systems to validate the sensor's performance and accuracy across a range of vibration frequencies and amplitudes. A series of tests such as sweep sine test, dwell sine test, classical shock test and random shock test were conducted. Results from various vibration test demonstrate the sensor's effectiveness in providing real-time vibration data, showcasing its potential for applications in predictive maintenance, structural analysis, and environmental monitoring. The wireless connectivity not only streamlines data collection but also enhances the scalability of the sensor network for large-scale deployments. In conclusion, the presented wireless vibration sensor system represents a significant advancement in the field of sensor technology, offering a reliable and versatile solution for monitoring vibrations in diverse settings. The findings of this research contribute to the ongoing efforts in improving the efficiency and accessibility of sensor systems for a wide range of applications